The understanding of integrity among public agencies in Kota Samarahan / Lene Lamat - Lamat, Lene; Isa, Melvin Dunggau (2015)
This section focuses on the background of the study, which is about the understanding of integrity among public servants in Kota Samarahan. Section 1.1 is discussing about the background of the study, Section 1.2 is focusing on the problem statement, and Section 1.3 states the research questions. Section 1.4 explains about the research objectives, Section 1.5 is explaining about the scope of our study. Section 1.6 is focusing on the significance of the study and Section 1.7 is focus on limitation of study. Finally, Section 1.8 explains about the definitions of terms and concepts.